Asia Pacific Regional Organisations and Japanese Domestic Law - Hotta, Makitaro (Victoria University of Wellington Law Review, 1998)
This is the first part of a two part article on the impact of regionalisation on domestic legal systems with reference to Japan. Part I deals with international and regional organisations and their structure. Domestic legal issues in Japan under Asia Pacific regionalism will be examined in Part II, with particular reference to human rights issues and will be published in the next issue of the Yearbook.